Bio-degradation of polyhydroxyalkanoates (PHA) films in soil and lake environment - Sevakumaran Vigneswari,; Nurul Shuhada Rashid,; Al-Ashraf Abdullah Amirul, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The use of petroleum-based synthetic plastics has led to a deleterious solid waste management especially in the form of marine debris and presents a major growing global pollution problem. In response to these issues, the application of biobased and biodegradable polymers as an alternative to synthetic plastics has been proposed. Polyhydroxyalkanoates (PHA) is a biodegradable microbial polymer. In this study, the biodegradation of this PHA both in soil and lake environment was evaluated. The percentage of degradation of the PHAs with various monomers such as poly (3-hydroxybutrate) [P(3HB)] and its copolymers poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB] in soil and lake was carried out. Besides, the modifications of these biopolymers into salt-leached films were also tested. Based on the results obtained, P(3HB-co- 4HB) films showed the highest rate of degradation for both lake and soil environment. Also the degradation of PHA, mainly caused by microbial activity, isolation and identification microorganisms capable of degrading PHA was also carried out. Based on the degradation index, Pseudomonas species and Acidovorax species were isolated.